Atmospheric deposition of soluble trace elements along the Atlantic Meridional Transect (AMT). (November 2017) - Baker, Alex R.; Jickells, Tim D.
Highlights: New aerosol soluble trace metal data are provided along the AMT transect and compared to water column concentrations in the underlying waters. Atmospheric deposition of iron and aluminium clearly creates a surface water concentration signature, while the response for other metals and nutrients is not seen in surface water concentrations because of surface water biogeochemical processes. Abstract: We briefly review the role of atmospheric deposition measurements within the Atlantic Meridional Transect (AMT) programme and then go on to present new data on the soluble concentrations of a range of trace metals (Fe, Al, Mn, Ti, Zn, V, Ni and Cu) and major ions in aerosols collected along the AMT transect. The results allow us to identify emission sources of the trace metals particularly in terms of the relative importance of anthropogenic versus crustal sources. We identify strong gradients in concentrations and deposition for both crustal and anthropogenically sourced metals with much higher inputs to the North Atlantic compared to the South Atlantic, reflecting stronger land based emission sources in the Northern Hemisphere. We suggest anthropogenic sources of Ni and V may include an important component from shipping. We consider the extent to which these gradients are reflected in surface water concentrations of these metals based on the GEOTRACES water column trace metal data. We find there is a clear difference in the concentrations of surface water dissolved Al and Fe between the north and south Atlantic gyres reflecting atmospheric inputs. However for Mn, V or Ni, higher inputs to the North Atlantic compared to the South Atlantic are not clearly reflected in their water column concentrations.